Bridging Capital in Community Conservation: A Case Study of the Taos Community Conservation Plan. Issue 7 (3rd July 2022) - Waters, Andrew; Chancellor, Charles
Abstract: If the United States land trust movement can overcome decades of institutionalized discrimination, it must institute sustained bridging capital to neglected constituents. This qualitative case study employs community-based conservation research literature findings to examine the bridging efficacy of an equity-based conservation plan in Taos, New Mexico. Interviews were combined with related documents and researcher observation in qualitative analysis. Results indicate conventional planning tools were inadequate in bridging Taos's Hispanic community, although experiential opportunities at an associated park project showed greater promise. Findings support research indicating community bridging efforts should move away from instrumental efforts focused on specific outcomes toward ones that address agency issues in long-term, intrinsic trust-building processes. However, equity-based initiatives such as the TCCP can initiate other bridging capital benefits such as enhancing trust and consensus between groups and overcoming previous conflicts.